Biogenic amines in the testis: sources, receptors and actions - Frungieri, Monica Beatriz; Mayerhofer, Artur (Frontiers in Endocrinology, 2024)
Biogenic amines are signaling molecules with multiple roles in the central nervous system and in peripheral organs, including the gonads. A series of studies indicated that these molecules, their biosynthetic enzymes and their receptors are present in the testis and that they are involved in the regulation of male reproductive physiology and/or pathology. This mini-review aims to summarize the current knowledge in this field and to pinpoint existing research gaps. We suggest that the widespread clinical use of pharmacological agonists/antagonists of these signaling molecules, calls for new investigations in this area in order to evaluate the relevance of biogenic amines for human male fertility and infertility, as well as the potential value of at least one of them as an anti-aging compound in the testis.